Implicit-explicit power motives congruence and forgiveness in the workplace conflict: the mediating role of empathy. Issue 3 (29th January 2021) - Ran, Yaxuan; Liu, Qiaowei; Cheng, Qi; Zhang, Yishi
Abstract : Purpose: In the workplace, forgiveness can increase positive interactions between the victim and offender in the aftermath of a conflict. As an important intrapersonal factor in an organization, a victim's power motives may shape one's forgiveness. However, previous research shows inconsistent results because it only considers explicit power motives while ignoring the possible contingent role of implicit power motives in influencing forgiveness. This paper aims to consider both implicit and explicit power motives and aims to examine their joint effect on interpersonal forgiveness in the workplace conflict. Design/methodology/approach: Polynomial regressions with response surface analysis were conducted with 415 Amazon Mechanical Turk users. Implicit power motives were measured by using a modified picture story exercise technique, whereas explicit power motives were measured via self-response scales. Findings: First, congruence in power motives was associated with higher empathy and forgiveness than incongruence. In addition, high-implicit/high explicit power motives led to higher level of empathy and forgiveness than low-implicit/low-explicit power motives. Furthermore, directional power motive incongruence had an additive effect on forgiveness, such that discrepantly low-implicit/high-explicit power motives were more detrimental to empathy and forgiveness than discrepantly high-implicit/low-explicit power motives. Finally, empathy underlies the combined effect of implicit and explicit power motives on forgiveness. Practical implications: The findings suggest that in a workplace conflict, managers should consider an employee's explicit and implicit motives. To build the harmony group work climate, managers can improve intrapersonal implicit–explicit power motive congruence by providing developmental support and training focusing on self-enhancement and self-affirmation with the low-explicit-powerful employees. Further, to promote forgiveness in a conflict, organizations can use empathy-based exercise and provide team building activities to increase employees' empathy and perspective-taking toward others. Originality/value: By integrating implicit–explicit framework, this paper conciliates previous studies investigating the relationship between power and forgiveness by proposing that the two types of power motives, implicit and explicit power motives, jointly influences a victim's forgiving tendency. This study serves as a meaningful touchstone for future research to consider both implicit and explicit power motives into the organizational conflict framework.